UPAYA PENINGKATAN KEMANDIRIAN DAN KEWIRAUSAHAAN SISWA MELALUI PROGRAM SEKOLAH BERKEBUN - Rosmayati; Hasanuddin; Nini Rahmawati (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
OSIS and Production Unit SMKS IT Marinah Al-Hidayah Medan are two elements that work together in the development of SMKS IT Marinah Al-Hidayah Medan. Production Unit which is media for students to develop creativity, interests and talents as well as place students to add experience and income with entrepreneurship. The activities to be carried out are the cultivation of oyster mushrooms, the utilization of mushrooms baglog waste and agricultural waste as compost raw material for use as a medium in vertical agricultural systems. However, the problem faced is the difficulty of supplying good quality oyster mushroom independently and also limited information about the technical culture of oyster mushroom cultivation, baglog waste handling and agricultural waste and utilization of school land for vegetable cultivation by vertikultur method. To help overcome these problems, the community service team of the Faculty of Agriculture USU through the Garden School Program conducts training on producing good quality oyster mushroom seeds by introducing mushroom seed making tools, press baglog and 20 m2 of growing room. Wastes baglog mushrooms and agricultural waste from around the school environment then processed into compost using compost machine. The resulting compost is used as a medium for planting organic vegetables using vertikulture cultivation system. Students are also trained to process a variety of food products made from oyster mushroom so that the shelf life, nutritional content and economic value of oyster mushrooms can be increased so it can be marketed to train to increase self-reliance with entrepreneurship.